The Effects of Sit-to-Stand Training Combined with Real-Time Visual Feedback on Strength, Balance, Gait Ability, and Quality of Life in Patients with Stroke: A Randomized Controlled Trial - Seung-Jun Hyun (MDPI AG, 2021)
This study aimed to investigate the effects of lower limbs muscles’ strength, balance, walking, and quality of life through sit-to-stand training combined with real-time visual feedback (RVF-STS group) in patients with stroke and to compare the effects of classic sit-to-stand training (C-STS group). Thirty patients with stroke were randomly divided into two groups. The RVF-STS group received sit-to-stand training combined with real-time visual feedback using a Wii Balance Board (n = 15), and the C-STS group received classic sit-to-stand training (n = 15). All participants received training for 20 min once a day, 5 days a week for 6 weeks, and both groups underwent general physical therapy for 30 min before training. Before and after the training, the muscle strength of the hip flexor, abductor, and knee extensor were measured, and the Wii Balance Board was used to perform the center of pressure test and Berg Balance Scale to evaluate static and dynamic balance. Additionally, the 10 m walking test and the Timed Up and Go test were performed to evaluate gait function. The Stroke-Specific Quality of Life was used to measure the quality of life. The results showed that the lower extremity muscle strength, balance ability, walking ability, and quality of life of the RVF-STS group significantly improved in comparison of the pre- and post-differences (p < 0.05), and it also showed significant differences between groups (p < 0.05). This study showed that sit-to-stand training combined with real-time visual feedback was effective at improving the muscle strength of the lower extremities, balance, gait, and quality of life in patients with stroke. Therefore, repeating sit-to-stand training combined with real-time visual feedback could be used as an effective treatment method for patients with stroke.